2021
DOI: 10.1088/1361-6641/ac17a8
|View full text |Cite
|
Sign up to set email alerts
|

Optical property of hexagonal (2H) silicon crystal

Abstract: Hexagonal (2H) silicon (Si) semiconductors have excellent mechanical properties and optically diverse applications due to their structure and quasi-direct bandgap. The 2H-Si has a relatively lower direct band gap of approximately 1.69 eV at the Γ-point in comparison with that of diamond-silicon (i.e. 3.4 eV), but it is not actually a direct bandgap semiconductor. Herein, we report an optical property of wide spectrum light emission in visible and infrared ranges from grown Si crystals with a 2H structure of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Therefore, the Si micro single-crystal light-emitting device is considered by the spectrum of EL rather than light emission by Joule heat like a filament. The main peak at 763 nm (1.625 eV) shows a characteristic similar to about 1.70 eV theoretically predicted as a quasidirect bandgap for the characteristic of the 2H-hexagonal Si structure [5,17,20,53,[61][62][63][64]. Figure 11(j) shows the Commission international de l'Eclairage (CIE) color coordinates for visible light emission of a Si single crystal.…”
Section: Performance Of Light Emission Of Si Crystalsupporting
confidence: 61%
See 3 more Smart Citations
“…Therefore, the Si micro single-crystal light-emitting device is considered by the spectrum of EL rather than light emission by Joule heat like a filament. The main peak at 763 nm (1.625 eV) shows a characteristic similar to about 1.70 eV theoretically predicted as a quasidirect bandgap for the characteristic of the 2H-hexagonal Si structure [5,17,20,53,[61][62][63][64]. Figure 11(j) shows the Commission international de l'Eclairage (CIE) color coordinates for visible light emission of a Si single crystal.…”
Section: Performance Of Light Emission Of Si Crystalsupporting
confidence: 61%
“…A mixed-source HVPE approach was used to grow the Si crystals. Mixed source HVPE is a process that involves the mixing of metal raw materials in a single well of a boat [5]. Si, Ga, and metal Al were used as the mixed source in the current study, as shown in figure 1(a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem can be solved by switching to other silicon allotropes, many of which possess intriguing optical and electrical properties [2][3][4][5], including direct and quasidirect transitions [6][7][8][9]. For example, hexagonal Si-IV was shown to exhibit intense luminescence on the edge of the visible spectrum, with an energy of 1.5 eV [10].…”
Section: Introductionmentioning
confidence: 99%